2001
DOI: 10.1111/j.1469-8749.2001.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Hip pain in 234 non‐ambulatory adolescents and young adults with cerebral palsy: a cross‐sectional multicentre study

Abstract: In orthopaedic clinical practice hip pain is the main complaint of adults with cerebral palsy (CP). The aim of this descriptive study was to specify prevalence of hip pain and to propose methods of care other than surgery. The study was a cross sectional multicentre one based in the Rhône‐Alpes region. Patients over 15 years of age, with CP who were non‐ambulatory were included. Two hundred and thirty‐four patients were questioned. Mean age of the patients was 27 years 10 months, median 26 years 1 month, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 20 publications
(17 reference statements)
1
41
0
2
Order By: Relevance
“…34 Movement disorders associated with CP (ie, spasticity, dystonia, athetosis) are thought to lead to musculoskeletal pain later in life due to relative overuse, lack of active position changes, and/or abnormal forces across joints. 35 Supporting this premise, Hodgkinson et al 35 reported that 47% of sample of 234 nonambulatory adults with CP reported hip pain. In a preliminary sample of 20 children and adolescents with CP, Engel et al 36 recently documented that 70% of the sample experienced recurrent chronic pain of moderate intensity on a daily or weekly basis.…”
Section: Discussionmentioning
confidence: 71%
“…34 Movement disorders associated with CP (ie, spasticity, dystonia, athetosis) are thought to lead to musculoskeletal pain later in life due to relative overuse, lack of active position changes, and/or abnormal forces across joints. 35 Supporting this premise, Hodgkinson et al 35 reported that 47% of sample of 234 nonambulatory adults with CP reported hip pain. In a preliminary sample of 20 children and adolescents with CP, Engel et al 36 recently documented that 70% of the sample experienced recurrent chronic pain of moderate intensity on a daily or weekly basis.…”
Section: Discussionmentioning
confidence: 71%
“…14,15 Hip surveillance programs consisting of routine hip x-rays help to identify subluxation and allow for a range of interventions, such as stretching, hip abduction bracing, botulinum toxin, and orthopedic surgery, before hip dislocation and chronic pain develop. 16 Evidence from this study suggests that hip subluxation should routinely be assessed and, if present, management strategies should be actively introduced.…”
Section: Discussionmentioning
confidence: 99%
“…The changes become noticeable around the age of two and the risk of hip dislocation is highest before seven years of age [1]. Hip migration and/or displacement can cause severe pain, loss of seating balance and comfort, progression of scoliosis (if present), whereas progressive hip contracture makes hygiene difficult [2,3]. However, advanced hip lateralization is preventable and successful screening programs have been developed based on repeated clinical and radiological (X-ray) evaluations, typically in 6-8-month intervals and, where needed, introduction of early preventive treatments [4][5][6].…”
Section: Introductionmentioning
confidence: 99%